コクサイ チキュウ ジキケン カンソク ケイカク IMS キカンチュウ ノ ナンキョク ロケット ジッケン ホウコク 1976-1978 - 鮎川, 勝; アユカワ, マサル; 平沢, 威男; ヒラサワ, タケオ; AYUKAWA, Masaru; HIRASAWA, Takeo (1980)
P(論文) 国際地球磁気圏観測計画(IMS)に対応し,3年間にわたって昭和基地で実施されたロケットによるオーロラ観測に関しての報告である.特に,計画の立案,諸準備・訓練の経過,新型ロケット(S-310JA型)の輸送法,昭和基地ロケット施設の改造・保守,ロケット打ち上げ経過,飛しょう結果などについて報告し,今後のロケット実験に資することを期した. During the period of International Magnetospheric Study (IMS, 1976-1979), twelve S-210JA type and seven S-310JA type rockets were launched from Syowa Station, Antarctica, into auroras at various stages of polar substorms. Through the successful rocket flights, the significant physical quantities in auroras were obtained. The present paper mainly reports on the progress of the research program by means of sounding rocket at Syowa Station concerning the preparation and transportation of the rockets, the maintenance of the launching facilities, arrangements of the rocket firing and tracking and the obtained results of the rocket flights. departmental bulletin paper